Desired and unwanted brotherhood Book review edited by Joanna Kulska and Anna M. Solorz Fraternity as an Overlooked Element in Global Politics, Routledge 2025 - Szymborska, Maria (Chrześcijaństwo-Świat-Polityka, 2025)
The article is a review of Fraternity as an Overlooked Element in Global Politics, a publication edited by Joanna Kulska and Anna M. Solorz and published by Routledge in 2025. An international group of scientists analyse the meaning and inclination of fraternity as an element of political thought.